Surgical Outcomes of Endoscopic Endonasal Versus Transcranial Resection of Craniopharyngiomas. (16th November 2020) - Domingo, Ricardo; Akinduro, Oluwaseun; Sandhu, Sukwinder; Lu, Victor M; Vivas-Buitrago, Tito; Herrera, Juan P; Chaichana, Kaisorn L; Quinones-Hinojosa, Alfredo
Abstract: INTRODUCTION: Surgical resection of craniopharyngiomas (CPs) is challenging due to their close relationship to neurovascular structures and extension to multiple intracranial compartments. CPs can be effectively resected via an endoscopic endonasal approach (EEA), or via an open transcranial approach (TCA), but there is no clear consensus as to the optimal surgical strategy for resection of these tumors. METHODS: We identified and reviewed 198 electronic medical records from patients with confirmed diagnosis of CP who underwent surgical resection at 3 tertiary care institutions from 2004 to 2018. Outcome comparisons between TCA versus EEA resection groups were conducted using chi-square exact test and Wilcoxon rank-sum test for categorical and continuous data, respectively. To control for potential preoperative clinical differences between the cohorts, matched pairs were created for matched-pair analysis by matching age, gender, and tumor volumes of an EEA patient with a TCA patient. RESULTS: After appropriate exclusion criteria, 121 patients with a confirmed diagnosis of CP who underwent first time surgical resection at our institutions were included. 90(74.4%) and 31(25.6%) patients underwent TCA and EEA, respectively. In a matched-pair analysis of 31 matched pairs (62 patients), the EEA was significantly associated with a increased CSF leak rate ( P  = .02), and decreased length of stay ( P  < .01), while the TCA group was associated with a higher rate of post-operative worsening of visual fields ( P  < .04) and post-operative complications ( P  < .04). No statistically significant difference was seen in histopathologic subtype (p = 0.16), EOR (p = 0.29), post-operative panhypopituitarism (p = 0.26), post-operative diabetes insipidus (0.43), new-onset obesity (0.91), recurrence rates (p = 0.75), or adjuvant therapy (p = 0.33). CONCLUSION: Patients with EEA had a significantly decreased length of stay and a higher rate of CSF leaks, while the TCA led to an increased risk of worsened vision and post-operative complications. The ideal surgical approach for patients with CP should be chosen on a case-by-case basis.